Analysis of the Application of SAK EMKM in Small and Medium Enterprises Panglong Karya Pribumi Aek Kuasan District, Asahan Regency - Syahputra, Dimas; Nurbaiti; Syafina, Laylan (Universitas Dehasen Bengkulu, 2023)
The purpose of this study was to analyze the suitability of financial statements based on the application of accounting based on SAK EMKM to UKM Panglong Karya Pribumi Jln Besar Sengon Sari No 21 Dusun II, Aek Kuasan District, Asahan Regency. This research was conducted using a qualitative method with a descriptive approach and the application of recording financial statements based on SAK EMKM using primary and secondary data taken from UKM Panglong Karya Indigenous. The data collection technique in this study used observation, interview and documentation techniques and the analysis technique used was data reduction, data presentation and conclusion. Based on data analysis, the results of the study show that Panglong Karya Indigenous UKM have implemented accounting but the recording of financial reports is still done manually and is very simple and its application does not follow the provisions in SAK EMKM. The financial statements made by UKM Panglong Karya Pribumi are only in the form of a profit and loss statement, while there is no report on financial position and notes on financial statements. The obstacle that caused the Panglong Karya Indigenous UKM to not implement was that they did not know and understand the preparation of business financial reports based on Micro, Small, Medium Entity Financial Accounting Standards (SAK EMKM).